Tocotrienol-rich fraction supplementation modulates antioxidant enzymes activity and reduces DNA damage in APPswe/PS1dE9 Alzheimer’s Disease Mouse Model - H.A. Damanhuri,; N.I. Abdul Rahim,; W.N. W Nasri,; Tan, J.K.; S. Makpol,; M. Mazlan,; Tooyama, I.; W.Z. Wan Ngah, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by deterioration of the brain functions that result in impairment of memory, cognition and behavioural functions. Oxidative stress is well known to be one of the causative factors for AD. Thus this disease is potentially modulated by natural antioxidants such as vitamin E. The aim of this study was to evaluate the effect of tocotrienol-rich fraction (TRF) supplementation on antioxidant enzymes and DNA damage using APPswe/PS1dE9 transgenic mouse model of AD. Animals were supplemented with TRF (200 mg/kg) or alpha-tocopherol (αT) (200 mg/kg) for six months starting from nine months old. We found that superoxide dismutase (SOD) activity in AD mouse was decreased by supplementation of TRF and αT as compared with AD control mouse with no significant differences in glutathione peroxidise (GPx) activity in all groups. TRF supplementation significantly increased catalase (CAT) activity. The level of DNA damage of AD mouse shows significant decrease with supplementation of TRF and αT. In conclusion, TRF was able to modulate antioxidant enzymes activity and decreased the level of DNA damage of AD transgenic mouse model.